2022
DOI: 10.3390/ijerph191811258
|View full text |Cite
|
Sign up to set email alerts
|

Stressors, Psychological States, and Relationship Quality among East Malaysian Adults with Partners Amid the COVID-19 Lockdown

Abstract: The COVID-19 pandemic has had a huge impact not only on healthcare systems and economic threats but also on relationships. Due to the massive measures of the Movement Control Order, such as social distancing, strictly limited physical activities, and making adjustments to working from home—merged with the pandemic’s fear—romantic partners may face challenges that affect the quality of their relationships. The purpose of this study was to (i) identify stressors experienced by participants during the COVID-19 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Pandemic-related disruptions in social connections are well documented, including limited social contact, reduced access to social support, restricted in-person interactions, and COVID 2024, 4 changes to communication means and frequency [8]. These disruptions resulted in increased loneliness and adverse impacts on wellbeing [7,9,10]. Increases in extreme social disruptions, including domestic conflict and violence, were also reported [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandemic-related disruptions in social connections are well documented, including limited social contact, reduced access to social support, restricted in-person interactions, and COVID 2024, 4 changes to communication means and frequency [8]. These disruptions resulted in increased loneliness and adverse impacts on wellbeing [7,9,10]. Increases in extreme social disruptions, including domestic conflict and violence, were also reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic responses increased parental caregiving demand or responsibility while also reducing access to supports, thereby increasing strain and decreasing opportunity for reprieve [14]. Pandemic responses indirectly affected national and international economies as well as individual and family finances with decreasing or cessation of income, due to job loss, being high-risk if infected with COVID, or illness resulting from COVID infection [4,10]. Impacts on economies indirectly affected individuals through job instability and disruptions to supply chains and access to consumer goods [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that these studies predominantly offered cross-sectional insights, while a singular longitudinal study revealed there were no changes in couple satisfaction over a one-year follow-up period (Galdiolo, et al, 2022). Notably, some reports surfaced regarding enhancements in relationship quality during lockdown measures, particularly in areas of commitment, trust, passion, love, and sexual intimacy (Mutang, et al, 2022), specifically for newlyweds (Williamson et al, 2021). These differences in results could be due to how the couple grappled with preexisting stressors, sociodemographic characteristics, and personal vulnerabilities (Overall et al, 2022;Pietromonaco & Overall, 2021).…”
Section: Introductionmentioning
confidence: 99%